Association of Platelet Indices with Severity and Prognosis of Acute Ischemic Stroke - لايقة, عيسى; الشمالي, سوزان; النقري, سليمان (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: Platelet indices reflect the function and activity of platelets. Results from most international studies about the association of platelet indices and acute ischemic stroke are still conflicting. Our goal in this study was to identify an association between platelet indices and the severity and prognosis of acute ischemic stroke. Methods: We studied 156 patients with acute ischemic stroke who were admitted to the neurology unit in Tishreen University Hospital during the period from August 2019 to July 2020, and compared them with 113 control subjects. The severity of ischemic stroke was evaluated according to NIHSS, and patients were stratified in prognostic groups based on mRS. Platelet indices in patients were determined 48 hours or less after the onset of symptoms. Results: There was a negative correlation between platelet count and acute ischemic stroke (246.7±77.9×109Ł in patients vs. 267.9±84.6×109Ł in controls, p-value=0.03). There was a statistically significant association between higher Mean Platelet Volume (MPV) values and acute ischemic stroke (11.3±2.8 fL in patients vs. 8.9±2.8 fL in controls, p-value=0.02). There was also an association between MPV and the severity of ischemic stroke (11.1±1.4 fL in severe ischemic strokes, p-value=0.03). MPV was also related to the prognosis of acute ischemic stroke (11.2±1.1 fL in bad prognosis group according to mRS, p-value=0.03).